NILAI-NILAI PENDIDIKAN AGAMA ISLAM DALAM BUKU SENI MERAYU TUHAN KARYA HABIB HUSEIN JA’FAR AL-HADAR - Ummi Farwah; Eka Naelia Rahmah (Fakultas Tarbiyah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2023)
The purpose of this study was to find out and describe the values ​​of Islamic religious education contained in the book The Art of Seducing God by Habib Husein Ja'far Al-Hadar. The research method used is a qualitative research method with a descriptive approach. Here the author collects some data in the form of books and journals that discuss Islamic Religious Education contained in the book The Art of Seducing God. In this study, the authors used a type of library research or what is often referred to as library research. The author utilizes library resources to obtain research data, and limits activities only to library collection materials without the need for field research. The results of this study indicate that in the book The Art of Seducing God, there are values ​​of Islamic Religious Education, namely the first, the value of faith which explains the meaning of Tawheed to Allah by recognizing the attributes of His majesty, believing in the Messenger of Allah, believing in destiny and the last day. Second, the value of moral education is in the form of morals when worshiping Allah, morals towards creatures by respecting and respecting each other according to Islamic teachings. Third, the value of beauty, and fourth the value of brotherhood (ukhuwah). The contents of the book The Art of Seducing God relate religious teachings to all things in life but are still by the objectives of Islamic religious education.